Petrology, Minerals chemistry and Geochemical relationships of the Sheared Gabbro Rocks in Alanah (Beesha) area within Erbil Governorate, NE Iraq - Harith E. Al-Jubury; Mazin Y. Tamr Agha; Ahmed M. Aqrawi (Academic Science Journal)
The current research is seeking to identify the petrography, mineralogy and geochemical relationships of Gabbro rocks in Besha area within Erbil Governorate, at the Unstable Shelf in Imbricate Zone. This study aims to determine the origin of the gabbroic rocks and their geochemical relationships.